Parents’ Perceptions of Strengthening Islamic Religious Education in the Digital Era in Tanjung Mulia Subdistrict - Icha Puspita Sari; Afrahul Fadhila Daulai; Humaidah Br. Hasibuan (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to describe parents’ perceptions of strengthening Islamic Religious Education (PAI) for children in the digital era in Tanjung Mulia Village, as well as to identify the forms of reinforcement applied by parents and the supporting and inhibiting factors involved. This research employs a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation involving parents of children aged 6–14 who actively use digital technology. The findings indicate that most parents hold positive perceptions regarding the importance of strengthening Islamic education, as technological advancement significantly influences children’s morals and behavior. The forms of reinforcement implemented by parents include religious habituation, role modeling, supervision of gadget use, and the utilization of Islamic digital applications and media to support religious learning. Supporting factors include the availability of Islamic digital resources, parental awareness, and a religious family environment. Meanwhile, inhibiting factors consist of parents’ limited digital literacy, children’s gadget dependency, and parents’ busy schedules that reduce direct interaction with their children. This study concludes that strengthening Islamic education in the digital era requires a synergy of parental role modeling, supervision, and digital literacy to ensure that technology contributes positively to children’s religious character development.